Evaluating the post-discharge cost of healthcare-associated infection in NHS Scotland. (August 2021) - Manoukian, S.; Stewart, S.; Graves, N.; Mason, H.; Robertson, C.; Kennedy, S.; Pan, J.; Haahr, L.; Dancer, S.J.; Cook, B.; Reilly, J.
Summary: Background: Whereas the cost burden of healthcare-associated infection (HAI) extends beyond the inpatient stay into the post-discharge period, few studies have focused on post-discharge costs. Aim: To investigate the impact of all types of HAI on the magnitude and distribution of post-discharge costs observed in acute and community services for patients who developed HAI during their inpatient stay. Methods: Using data from the Evaluation of Cost of Nosocomial Infection (ECONI) study and regression methods, this study identifies the marginal effect of HAI on the 90-daypost-discharge resource use and costs. To calculate monetary values, unit costs were applied to estimates of excess resource use per case of HAI. Findings: Post-discharge costs increase inpatient HAI costs by 36%, with an annual national cost of £10, 832, 437. The total extra cost per patient with HAI was £1, 457 (95% confidence interval: 1, 004–4, 244) in the 90 days post discharge. Patients with HAI had longer LOS if they were readmitted and were prescribed more antibiotics in the community. The results suggest that HAI did not have an impact on the number of readmissions or repeat surgeries within 90 days of discharge. The majority (95%) of the excess costs was on acute care services after readmission. Bloodstream infection, gastrointestinal infection, and pneumonia had the biggest impact on post-discharge cost. Conclusion: HAI increases costs and antibiotic consumption in the post-discharge period. Economic evaluations of IPC studies should incorporate post-discharge costs. These findings can be used nationally and internationally to support decision-making on the impact of IPC interventions.